Pathways for marine carbon dioxide removal using electrochemical acid-base generation - Eisaman, Matthew D. (Frontiers in Climate, 2024)
Research over the past decade has resulted in various methods for removing CO2 from the atmosphere using seawater and electrochemically generated acids and bases. This Perspective aims to present a unified framework for comparing these approaches. Specifically, these methods can all be seen as falling into one of two categories: those that result in a net increase in ocean alkalinity and use the “ocean as a sponge” for atmospheric CO2 (ocean alkalinity enhancement, or OAE) and those that cycle ocean alkalinity and use the “ocean as a pump” for atmospheric CO2 (ocean alkalinity cycling, or OAC). In this Perspective, approaches for marine carbon dioxide removal (mCDR) using electrochemistry are compared using this framework, and the similarities and differences of these two categories are explored.